2007
DOI: 10.1111/j.1365-2842.2007.01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Candida and nocturnal denture wear: quantitative study

Abstract: The purpose of this study was to evaluate the relationship between Candida and denture wear during the night. Twenty-four edentulous volunteers were randomly divided into two groups. Group I (GI, n = 11) was composed of volunteers who wore their complete dentures day and night and Group II (GII, n = 13) was composed of volunteers who wore their complete dentures only during the day. Three examination periods were performed for both groups. In GI, the first examination (A) was carried out after overnight dentur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 34 publications
3
47
1
5
Order By: Relevance
“…Thus, the mechanical cleaning combined with effective and inexpensive chemical aids, such as sodium hypochlorite and coconut soap, seems to be more appropriate (15). Although the habit of wearing dentures during sleep is important on DML development, especially denture stomatitis (16), this study did not find a statistical association between these variables. According to Emami et al (17), nocturnal wearing of the dentures can reduce the protective effect of saliva, by cleaning the tongue, and good oxygenation of the mucosa, which are key factors in the resistance of mucosal tissue to mechanical and microbiological aggression.…”
Section: Discussioncontrasting
confidence: 58%
“…Thus, the mechanical cleaning combined with effective and inexpensive chemical aids, such as sodium hypochlorite and coconut soap, seems to be more appropriate (15). Although the habit of wearing dentures during sleep is important on DML development, especially denture stomatitis (16), this study did not find a statistical association between these variables. According to Emami et al (17), nocturnal wearing of the dentures can reduce the protective effect of saliva, by cleaning the tongue, and good oxygenation of the mucosa, which are key factors in the resistance of mucosal tissue to mechanical and microbiological aggression.…”
Section: Discussioncontrasting
confidence: 58%
“…First, even in a healthy older adult, aspiration of unnoticed oropharyngeal and periodontal secretions occurs during sleep, and a high incidence of silent aspiration is strongly related to pneumonia among the elderly (Kikuchi et al 1994), particularly those with dementia or cerebrovascular disease. Denture wearing during sleep was reported to be associated with poor denture hygiene, oral candidiasis (Compagnoni et al 2007), and denture stomatitis (Baran and Nalçaci 2009;Fenlon et al 1998;Shulman et al 2005;Vigild 1987), all of which may function as reservoirs of potentially infectious pathogens (Sumi et al 2010). Our findings that denture wearers during sleep had significantly higher rates of denture and tongue plaque and oral candidiasis provide additional evidence for this suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…Another habit for the maintenance of complete dentures, overnight removal, was previously tested by another trial and associated with lower counts of Candida spp. if compared with continuous wearing (34). Previous studies which employed DNA checkerboard hybridization found differences among specific areas of the edentulous mouth (29), as well as changes after the insertion of dental implants (35).…”
Section: Discussionmentioning
confidence: 99%